Peran Brand Awareness, Perceived Value, dan Brand Uniqueness dalam meningkatkan Brand Loyalty pada Industri Fast Fashion - Ruslim, Tommy Setiawan; Febrian, Ferdy; Suryawan, Ian Nurpatria (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Fast fashion is a term used to describe a highly profitable business model based on imitating catwalk trends and high fashion designs, and mass-producing them at a low cost. One of the famous fast fashion brands in Indonesia is XYZ. But in the past few years, XYZ’s brand value has decreased. The purpose of this research is to examine whether 1) brand awareness can influence brand loyalty. 2) perceived value can influence brand loyalty. 3) brand uniqueness can influence brand loyalty. Purposive sampling method used by distributing online questionnaire with a sample of 208 respondents and then processed by using smartPLS- SEM. The result of this study indicate that brand awareness, perceived value, and brand uniqueness have a positive and significant influence towards brand loyalty.